Sweden : Technical Assistance Report-Proposed Amendments to the Riksbank Act. (IMF Staff Country Reports; Country Report ;, 2020)
At the request of the central bank of Sweden (the Riksbank), the Monetary and Capital Markets Department (MCM) provided technical assistance (TA) on central bank operations by means of a desk review of the proposed amendments suggested by the independent committee to the Swedish Riksbank Act, during the period February 2019 and June 2020. The desk review was led by Mr. Ashraf Khan, and conducted jointly with Mr. Asad Qureshi, Mr. Romain Veyrune, and Mr. Rudy Wytenburg. Additional input was also provided by Ms. Ioana Luca of the IMF's Legal Department and colleagues from the IMF's European Department, Sweden Team. The purpose of the desk review was to provide advice to the Riksbank on key issues relating to central bank operations, with a particular focus on the central bank's governance, independence, instruments, and internal organization. It should be noted that the review findings, comments, and recommendations in this report are not representative of views of the IMF or of its Executive Board and are intended for the purpose of contributing to the public discussion in Sweden in the context of the draft Riksbank Act. The comments are also not intended to be complete, nor represent a detailed legal review of the Act. Instead, as noted above, the comments reflect selected key issues from a central bank operations' perspective.